Daisy Cooper's rules for living - Keily, Tamsin (Park Row Books, 2020)
"Daisy Cooper's life is just getting started, when suddenly it ends. Surprised to find herself in an Afterlife processing center, she is even more stunned to learn that she wasn't meant to die for another fifty years. One terrible, embarrassing clerical error is behind it--and an administrator named Death is to blame. But death, as they say, is final, and Daisy must now navigate this impossible new world. With the help of an unlikely ally, Daisy begins to realize that letting go isn't just a challenge faced by those left behind. And as she learns how to survive this strange reality, friendship, hope and love begin to come alive in the most unexpected ways."--Amazon.